N2-(1-Carboxyethyl)deoxyguanosine, a nonenzymatic glycation adduct of DNA induces single strand breaks and increases mutation frequencies - Pischetsrieder, Monika; Seidel, Wolfgang; Münch, Gerald; Schinzel, Reinhard (Biochemical and Biophysical Research Communications, 1999)
N2-(1-Carboxyethyl)deoxyguanosine (CEdG) is a major nonenzymatic glycation product of DNA. The effect of CEdG modification, which was specifically prepared by incubation with dihydroxyacetone, on plasmid DNA topology was evaluated by gel electrophoresis. A time-dependent decrease of supercoiled plasmid-DNA was observed in parallel to the increase of CEdG adducts; the half-life time of the supercoiled plasmid-DNA was estimated to be approximately 16-18 h. CEdG-modified plasmid DNA showed a 25-fold re duced transformation efficiency. When modified DNA was used to transform Escherichia coli cells, a 6-fold increase in mutation frequency was determined by measuring loss of alpha-complementation. For the mutator strain BMH71-18mutS, an 8-fold increase in mutation frequency was observed. Although the exact mechanism of DNA damage is unclear, the occurrence of spontaneous depurination is likely. These findings suggest that a defined DNA glycation reaction can lead to DNA damage in vivo.
UnivIS-Import:2015-03-05:Pub.1999.nat.dchph.llmch.n21car